Master planning for sustainability: envisioning the future our community colleges - Van Duyne, Wendy; Ammann, Darron (Kansas State University, 2011)
With the spotlight shining even more brilliantly on the benefits of attending community colleges versus traditional 4-year higher learning institutions, what role do these colleges play in leading our Kansas communities toward a more sustainable future? Community colleges have been receiving extra attention these days. Economic conditions have not only required most of us to tighten our wallets, but also re-evaluate the financial commitment we make to further our careers. Additionally, the economic downturn has strained the traditional commodities upon which our country has based its markets and is requiring that we take a second look at how green collar jobs and sustainable technologies can rebuild our economy. In a new world where innovative jobs must be invented to support this growth, our nation’s community colleges are rising to the challenge of educating tomorrow’s workforce. Kansas is in a unique position to support this effort and emerge as a leader in the sustainability education of its residents. With an expansive network of more than 19 community colleges, our State has a tremendous foundation upon which to establish this endeavor, and many of our colleges have already instituted programs and initiatives for green collar learning—such as the wind energy program at Cloud County Community College in Concordia. As our colleges grow to include the upswing in enrollment and program additions, how will the campus facilities support this expansion? How can our community colleges develop a plan that, not only anticipates the growth of the campus, but also actively engages the community stakeholders in the process? How can we provide Kansas community colleges with a roadmap to enthusiastically realize our sustainable future? Our presentation will outline the efforts that we’ve conducted to assist Cloud County Community College, Neosho County Community College, and Seward County Community College in developing a strategy and campus master plan that envisions the sustainable reality of these campuses for tomorrow.
Keywords: Master Planning; Sustainability; Community Colleges; Green collar jobs